1990
DOI: 10.1210/jcem-71-1-19
|View full text |Cite
|
Sign up to set email alerts
|

Sex Hormone-Binding Globulin Measurement in Patients with Inappropriate Secretion of Thyrotropin (IST): Evidence against Selective Pituitary Thyroid Hormone Resistance in Nonneoplastic IST*

Abstract: The differential diagnosis of the various forms of inappropriate secretion of TSH (IST), i.e. generalized thyroid hormone resistance (GRTH), selective pituitary resistance [non-neoplastic IST (nnIST)], and tumoral pituitary TSH hypersecretion [neoplastic IST (nIST)], mainly rests on clinical observation, skull imaging, and measurement of several parameters assessing peripheral thyroid hormone effects. Clinically, patients with GRTH usually display compensated hypothyroidism, while those with nnIST or nIST are … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
23
1
4

Year Published

1997
1997
2017
2017

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 88 publications
(30 citation statements)
references
References 26 publications
2
23
1
4
Order By: Relevance
“…However, recent data failed to demonstrate a direct role for estrogens in leptin regulation (27), but other reports indicated that variations in serum androgens cause leptin synthesis to be partially inhibited. Since both hypo-and hyperthyroidism cause variations in circulating sex hormone-binding globulin (28,29), as well as in peripheral sex hormone metabolism, the putative increase in or the relative prevalence of circulating androgenic compounds in female patients with thyroid disorders may account for the difference in SDS found in female patients.…”
Section: Discussionmentioning
confidence: 99%
“…However, recent data failed to demonstrate a direct role for estrogens in leptin regulation (27), but other reports indicated that variations in serum androgens cause leptin synthesis to be partially inhibited. Since both hypo-and hyperthyroidism cause variations in circulating sex hormone-binding globulin (28,29), as well as in peripheral sex hormone metabolism, the putative increase in or the relative prevalence of circulating androgenic compounds in female patients with thyroid disorders may account for the difference in SDS found in female patients.…”
Section: Discussionmentioning
confidence: 99%
“…In a subgroup of RTHβ patients, TA 3 is able to decrease TSH and consequently the high serum T 4 and T 3 levels. Since the thyromimetic effects of TA 3 itself do not fully compensate the reduction in endogenous TH levels, it alleviates the thyrotoxic symptoms including tachycardia, goiter, excessive sweating and behavioral problems (BeckPeccoz et al 1983, Lind & Eber 1986, Faglia et al 1987, Salmela et al 1988, Kunitake et al 1989, Smallridge et al 1989, Beck-Peccoz et al 1990, Aguilar Diosdado et al 1991 Crino et al 1992, Dulgeroff et al 1992, Ueda et al 1996, Darendeliler & Basx 1997, Radetti et al 1997, CliftonBligh et al 1998, Persani et al 1998, Asteria et al 1999, Kong et al 2005, Torre et al 2005, Wu et al 2006, Gurgel et al 2008, Santos et al 2008, Guran et al 2009, Anzai et al 2012, Ferrara et al 2012, Ramos-Prol et al 2013, Stagi et al 2014, Chatzitomaris et al 2015, Xue et al 2015. However, some patients do not respond to TA 3 treatment, which is assumed to depend on the type or location of the mutation (Hamon et al 1988, Persani et al 1998.…”
Section: Rthβmentioning
confidence: 99%
“…Studies have described SHBG in children and adults with THR and found that it was possible to distinguish patients with inappropriate TSH production (pituitary TSH-producing adenomas) from patients with THR. However, specificity was low in terms of distinguishing pituitary resistance from more generalized forms of THR [21,22]. …”
Section: Discussionmentioning
confidence: 99%